KUR Product Marketing Model at PT. UPS Bangkalan Sharia Pawnshop - Hariratun Hodro; Dahruji . (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2023)
Sharia pawnshops are financial institutions. this Financial Institution divided into two, namely Islamic financial institutions, banks and institutions Non-Bank Sharia Finance. Sharia financial institutions banks are bodies businesses that carry out activities in the financial sector by collecting funds, funds from the community in the form of savings and giving back society in the form of loans. Meanwhile, non-bank sharia financial institutions are businesses that operate in the financial sector, either directly or indirectly, collecting funds by issuing securities and distributing them to the public to finance company investments. Sharia pawnshops are part of non-bank companies intended for lower middle income people who need funds quickly and the process is quite short. This sharia pawnshop uses financing with a pawn system that complies with sharia principles. This research is analyzed in the marketing model in the implementation of KUR Syariah at PT. UPS Bangkalan Pawnshop. The results of the discussion of the KUR Syariah marketing model with the research method used are qualitative using the 7P Marketing Mix concept (Product, Price, Place, Promotion, People, Process, Physical Evidence). This research found that product strategy is carried out by maintaining and improving quality for customers. Pricing strategy, with Pegadaian Syariah becoming a non-bank company intended for lower middle class people who need funds quickly. This sharia pawnshop uses financing with a pawn system that complies with sharia principles